2021
DOI: 10.1002/cne.25102
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐protocadherin localization at the synapse is associated with parameters of synaptic maturation

Abstract: Clustered protocadherins (Pcdhs) are a family of ~60 cadherin‐like proteins (divided into subclasses α, β, and γ) that regulate dendrite morphology and neural connectivity. Their expression is controlled through epigenetic regulation at a gene cluster encoding the molecules. During neural development, Pcdhs mediate dendrite self‐avoidance in some neuronal types through an uncharacterized anti‐adhesive mechanism. Pcdhs are also important for dendritic complexity in cortical neurons likely through a pro‐adhesive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Several lines of evidence have pointed to clustered protocadherins as potentially important molecular players in synapse development, function, or maintenance in the mammalian nervous system. Indeed, Pcdhgs are found at synaptic clefts and enriched in postsynaptic density (PSD) fractions of synaptosomes (Loh et al, 2016; Phillips et al, 2003; Wang et al, 2002b; Weiner et al, 2005) and their presence is associated with synapse maturation (LaMassa et al, 2021; Li et al, 2010; Phillips et al, 2003). Moreover, many synapse-associated molecules are found in Pcdhg protein complexes, including PSD-95, α-catenin, and neuroligin-1 (Han et al, 2010; Molumby et al, 2017), suggesting that Pcdhgs may directly control or modulate synapse assembly or composition.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have pointed to clustered protocadherins as potentially important molecular players in synapse development, function, or maintenance in the mammalian nervous system. Indeed, Pcdhgs are found at synaptic clefts and enriched in postsynaptic density (PSD) fractions of synaptosomes (Loh et al, 2016; Phillips et al, 2003; Wang et al, 2002b; Weiner et al, 2005) and their presence is associated with synapse maturation (LaMassa et al, 2021; Li et al, 2010; Phillips et al, 2003). Moreover, many synapse-associated molecules are found in Pcdhg protein complexes, including PSD-95, α-catenin, and neuroligin-1 (Han et al, 2010; Molumby et al, 2017), suggesting that Pcdhgs may directly control or modulate synapse assembly or composition.…”
Section: Discussionmentioning
confidence: 99%
“…Gene knockout studies targeting each of the three cPcdh clusters have shown that cPcdh plays a role in multiple aspects of recognition events, including axonal projection, dendritic self-avoidance, dendritic arbor complexity, and synapse formation. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Mice lacking all 58 isoforms ( Δαβγ mice) exhibit the most severe phenotype. They die immediately after birth due to massive neuronal death and synaptic loss in the brainstem and spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted mechanical strength of the PCDHγB4 trans dimers, isolated and in junctions, is intriguing given that the clustered PCDHs mainly play a role in neuronal recognition (82,83), while the adherens junction and the desmosome maintain epithelial cell-cell adhesion and must withstand significant mechanical stress. The γ-PCDHs, of which PCHDγB4 is a member, might play a role in adhesion at the synapse (98,144), but it is difficult to say if the clustered PCDHs are under or respond to any mechanical strain in vivo. Perhaps this brittle response is appropriate for more subtle types of mechanical stimuli that clustered PCDHs may experience in neurons during development, normal function, and in brain injury (66)(67)(68)(69)(70)(71)(72)(73)76).…”
Section: Discussionmentioning
confidence: 99%
“…However, axon growth and neuronal circuit formation during brain development is a dynamic process in which mechanical forces play a role (66), and forcegenerating and load-bearing proteins are also thought to regulate synapse development and function (67)(68)(69), while action potentials can cause neuronal deformation (70)(71)(72)(73)(74)(75), and traumatic brain injury can disrupt neuronal adhesion (76). Interestingly, the clustered protocadherin (PCDH) proteins, a subtype of cadherins expressed predominantly in the nervous system (77)(78)(79)(80)(81)(82)(83), form adhesive junctions (84)(85)(86)(87)(88)(89)(90) thought to signal for self-avoidance (91)(92)(93) and that may also be involved in synapse maturation and function (94)(95)(96)(97)(98). The clustered PCDH junctions may need to withstand mechanical stimuli, albeit in a different cellular and functional context than classical cadherins.…”
Section: Introductionmentioning
confidence: 99%